On production efficiency of medical and biophysical isotopes using electron accelerator - Dikiy, N.P.; Dovbnya, A.N.; Maryokhin, S.V.; Uvarov, V.L. (Вопросы атомной науки и техники, 1999)
The results obtained demonstrate that using the high-current electron accelerator it is possible to produce a number of isotopes for medicine and biophysics.
The satisfactory agreement of experimental and computer simulation data demonstrates broad capabilities of the latter for optimization of the master schedules of isotope production on electron accelerators and solution accompanying heat-physics problems.